2016
DOI: 10.1111/jerd.12264
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Discoloration Potential for EndoSequence Bioceramic Root Repair Material Fast Set Putty and ProRoot MTA in Human Teeth: An In Vitro Study

Abstract: The results found in the present study suggest that PMTA produces tooth discoloration over time, whereas ERRMF does not induce tooth discoloration. Therefore, ERRMF might be an alternative to PMTA, especially for coronal restoration in aesthetic zone teeth. (J Esthet Restor Dent 29:59-67, 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
1
17
0
2
Order By: Relevance
“…, Alsubait et al . ). The reason that some studies did not find discolouration with Biodentine (Vallés et al .…”
Section: Important Clinical Factors and Possible Drawbacksmentioning
confidence: 97%
“…, Alsubait et al . ). The reason that some studies did not find discolouration with Biodentine (Vallés et al .…”
Section: Important Clinical Factors and Possible Drawbacksmentioning
confidence: 97%
“…Essa descoloração é consequência de compostos dos cimentos que se espalham em túbulos dentinários durante ou após sua adaptação 43 . Evidências suportam que materiais biocerâmicos poderiam induzir menor escurecimento da estrutura dentária 19,20 .…”
Section: Discussionunclassified
“…No entanto, mais estudos clínicos são necessários para confirmar esses achados 19 . Ao comparar o potencial de descoloração do Endosequence Bioceramic Root Repair Material Fast Set Putty (ERRM) e do ProRootMTA (PMTA), quando colocados coronalmente em dentes humanos extraídos durante um período de quatro meses, dentes em tratamento com PMTA exibiram descoloração progressiva, enquanto aqueles com ERRM mantiveram a estabilidade de cor 20 . …”
Section: Alteração De Corunclassified
“…It is also reported that BC is a bioactive cement [20] with similar compressive strength to MTA [21]. Furthermore, it does not induce discoloration in the tooth structure [18].…”
Section: Introductionmentioning
confidence: 87%
“…MTA has several desirable properties such as biocompatibility [14] and bioactivity [15]. The main disadvantages of MTA are the long setting time [16], difficulty in handling [17], and discoloration potential [18]. TotalFill BC (FKG, Dentaire, La Chaux-de-Fonds, Switzerland; marketed as EndoSequence BC from Brasseler USA in North America) is a newer calcium silicate-based cement that was developed to overcome the disadvantages of MTA.…”
Section: Introductionmentioning
confidence: 99%